2017
DOI: 10.1007/s11356-016-8311-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan

Abstract: Crop nutrient management is an essential component of any cropping system. With increasing concerns over environmental protection, improvement in fertilizer use efficiencies has become a prime goal in global agriculture system. Phosphorus (P) is one of the most important nutrients, and strategies are required to optimize its use in important arable crops like cotton (Gossypium hirsutum L.) that has great significance. Sustainable P use in crop production could significantly avoid environmental hazards resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Firstly, the promotional effects of N application is more easily observed than P. Secondly, cotton producers can have easier access to N than to P and K [10]. In recent years, China begins to pay more and more attention to the environmental problems caused by the overuse of N and the deficiency of P and K and cotton producers are encouraged to adopt a balanced application of N, P, and K [11].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the promotional effects of N application is more easily observed than P. Secondly, cotton producers can have easier access to N than to P and K [10]. In recent years, China begins to pay more and more attention to the environmental problems caused by the overuse of N and the deficiency of P and K and cotton producers are encouraged to adopt a balanced application of N, P, and K [11].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of high temperatures (45-48ºC) during the cotton-growing season, especially in the early and mid-season, limits potential yield of the cotton crop in this part of the world (Ali, Afzal, Ahmad, & Muhammad, 2009;Usman et al, 2009;Ali et al, 2010;2013a;2013b;Amin et al, 2017a;2017b). It is commonly understood that flowers appearing during July and August cannot produce good quality lint due to the poor opening of harvestable bolls under the prevalence of high temperatures during this growth period (Dong, Zhang, Tang, Li, & Li, 2005a;Dong, Li, Tang, Li, & Zhang, 2005b;Ali et al, 2010;Tariq et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lime content of soil greatly affects P availability (Abbaszadeh-Dahaji et al 2020;Delgado et al 2002). Amin et al (2017) suggested 57 kg P 2 O 5 ha −1 for obtaining maximum yield, while Hussain et al (2004) proposed 75-100 kg P 2 O 5 ha −1 for wheat. Even 90 kg P 2 O 5 ha −1 which exhibited about 90% of grain yield could be considered adequate.…”
Section: Discussionmentioning
confidence: 99%